Reversing VTN deficiency inhibits the progression of pancreatic cancer and enhances sensitivity to anti-PD1 immunotherapy - Zhao, Siqi; Gao, Zhaofeng; Hu, Lingyu; Li, Yihan; Wang, Xiaoguang; Li, Xiaoping; Chen, Minjie; Chen, Fei; Song, Zhengwei (Frontiers in Immunology, 2025)
BackgroundPancreatic cancer, a highly lethal malignancy with limited therapeutic options, necessitates the identification of novel prognostic biomarkers and therapeutic targets. The extracellular matrix protein vitronectin (VTN) has been implicated in tumor progression, but its specific role in pancreatic cancer progression and immunotherapy response remains unclear.MethodsThis study employed an integrative approach combining single-cell RNA sequencing, analysis of public databases, and functional assays. In vitro experiments assessed the impact of VTN knockdown and overexpression on pancreatic cancer cell proliferation, invasion, and migration. Mechanistic investigations explored associations between VTN expression and immune regulatory factors. A syngeneic mouse subcutaneous tumor model evaluated the therapeutic efficacy of VTN overexpression combined with anti-PD1 immunotherapy.ResultsVTN was significantly downregulated in pancreatic cancer tissues compared to normal tissues. Lower VTN levels correlated with poorer overall survival. VTN knockdown promoted pancreatic cancer cell proliferation, invasion, and migration in vitro, whereas VTN overexpression suppressed these phenotypes. VTN expression was linked to immune regulatory pathways. High VTN levels predicted improved survival in patients receiving anti-PD1/PD-L1 therapy. In a mouse model, VTN overexpression inhibited tumor growth and synergized with anti-PD1 therapy to enhance antitumor efficacy, suggesting combinatorial therapeutic potential.ConclusionsThis study identifies VTN as a dual-functional regulator in pancreatic cancer, acting as both a suppressor of tumor progression and a modulator of immunotherapy response. These findings position VTN as a prognostic biomarker and a therapeutic target to sensitize pancreatic tumors to anti-PD1-based immunotherapy, providing a potential strategy for overcoming treatment resistance in this aggressive malignancy.